The Etiological Spectrum of Febrile Encephalopathy in Adult Patients: A Cross-Sectional Study from a Developing Country - Elham Peidaee; Fereshte Sheybani; HamidReza Naderi; Nasrin Khosravi; Mehdi Jabbari Nooghabi (Emergency Medicine International)
The profile of febrile encephalopathy varies based on different demographic and geographical characteristics of the study population. This retrospective, cross-sectional study was conducted to evaluate the etiological spectrum of febrile encephalopathy in hospitalized adult patients. A total of 293 patients with the mean age of 49.7 ± 23 were evaluated of whom 77.1% presented with encephalopathy syndrome. The most common diagnosis in patients with clinical syndromes suggestive of central nervous system (CNS) infection was sepsis associated encephalopathy (SAE) (22.9%), followed by bacterial meningitis (14%) and neurotuberculosis (9.9%). The comparison between the elderly and young adults showed that, in the young adults, bacterial meningitis and neurotuberculosis, and in the elderly SAE, are among the most common causes of clinical syndromes suggestive of CNS infection including febrile encephalopathy in our region. Moreover, we illustrated an upward trend for the proportion of diagnosing CNS infections among those who underwent diagnostic LP, from 40.4% in 2011 to 70% in 2015, that could be indicative of an increasing threshold for performing LP at least in our center in recent years. Whether these changes have been associated with increasing the rate of diagnostic errors or not needs to be evaluated in future studies.